Pengaruh Corporate Social Responsibility terhadap Kinerja Keuangan Perusahaan - Trian Fisman Adisaputra; Suherwin; Nurarsy, Mutiara; Mariska, Lisa; Syam, Sarina; Azzahra, Aqmalia; Huda, Nurul; Agriyaningsih, Putri (Balanca : Jurnal Ekonomi dan Bisnis Islam, 2023)
Financial performance of a company refers to how well the company manages its financial statements accurately and appropriately. The purpose of this study is to determine the influence of Corporate Social Responsibility (CSR) on the financial performance of PT ABM Investama. In this study, the financial performance of the company is measured using Return On Assets (ROA) and Return On Equity (ROE). Furthermore, Corporate Social Responsibility (CSR) is used as an independent variable affecting Return On Assets (ROA) and Return On Equity (ROE). This research is a quantitative study that applies purposive sampling method. The sample selected is PT ABM Investama, which is listed on the Indonesia Stock Exchange, during the period of 2018-2021. This research utilizes multiple regression analysis method. The results of the study indicate that CSR has a positive and significant influence on Return On Equity (ROE), while CSR does not have a significant influence on Return On Assets (ROA).